FISH CONSUMPTION IN KERALA: EXTERNALITIES AND LESSONS LEARNED DURING COVID PANDEMIC - SALIM, SHYAM.S.; A. R. , ANUJA.; N. R , ATHIRA.; KUMARAN , AKHILA (Journal of the Inland Fisheries Society of India, 2026)
The COVID 19 pandemic induced stringent stress all across the food supply chain in the country causing perceptible changes in people's food consumption patterns. The spread of Corona virus has shaped tailbacks in the production, distribution and processing, leading to momentous shifts in fish consumption patterns as well as the demand and supply of fish. The present study analyses the changes in fish consumption patterns of Kerala state during three time periods viz, Pre COVID, COVID, and Post COVID in addition to assessing the determinants of fish consumption and the constraints towards fish consumption. The study was conducted in March 2022, using primary data gathered from the different households across Kerala with a total sample size of 440 across the state through a hybrid approach of online (Google Forms) and telephone questionnaire surveys. Qualitative, quantitative, and descriptive data analysis with statistical tools such as Wilcoxon's rank test and Maxdiff Cluster analysis was used for interpreting viable results for the study. The study identified that the consumption levels of fish during the COVID time have reduced considerably, thereby altering the consumption pattern and taste preferences. During the Pre COVID, most of the respondents consume fish daily (68.89 per cent), while in the pandemic phase, most of the respondents rely on weekly fish consumption of about 30.52 per cent. The consumption pattern has regained to a daily basis during the post-COVID COVID, however, there is a decrease to 30.52 per cent. The source of purchase has shifted from retail centres to online markets. The consumption of local fish increased due to the no availability and distortions in the supply chain. The  lockdown disruptions have severely affected the fish trade and thereby fish consumption. It was important to identify that the consumers resorted to less preferred fish from a known source rather than a preferred fish from an unknown source. Efforts to increase the local supply of fish with sufficient storage facilities were used to cope with such an unprecedented situation. However, more stringent measures should be identified with the governmental support of a resilient supply chain for enhancing the fish supply chain.